Effect of Artemisia persica on seizure severity and memory and learning disorders in pentylenetetrazole-kindled mice - Daneshkhah, Mozhgan; Setorki, Mahbubeh (Bangladesh Journal of Pharmacology, 2019)
The purpose of this study was to investigate the effect of hydroalcoholic extract of Artemisia persica (100, 200 and 400 mg/kg) on pentylenetetrazole-induced seizure and memory impairment. Sixty mice were assigned to seven groups. Pentylenetetrazole (35 mg/kg) was injected at 48 hours intervals for 9 days, and at 60 mg/kg on day 10 to induce seizure model. Different doses of A. persica extract were injected daily 30 min before pentylenetetrazole injection. Exposure of mice to extract significantly reduced the frequency of repeated spinning and jumping and tonic seizures in seizure model. In addition, the extract significantly reduced the increased levels of malondialdehyde in serum and brain. The extract significantly increased the serum and brain anti-oxidant capacity but had no significant effect on nitric oxide. The extract (100 mg/kg) significantly improved pentylenetetrazole-induced memory impairment. The hydro-alcoholic extract of A. persica has a protective effect against pentylenetrazole-induced seizure. Video Clip of Methodology: 1 min 56 sec: Click to watch